Pengembangan Instrumen Penilaian Keterampilan Berpikir Kreatif pada Mata Pelajaran IPA Terpadu Materi Atom, Ion, dan Molekul SMP Islam Al Falah - Siti Marwiyah; Kamid Kamid; Risnita Risnita (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2015)
The purpose of this study was to develop an assessment instrument to measure creative thinking skills of junior high school students on integrated science of atom, ion, and molecules material. The instrument consists of a number of questions that require creative thinking skills and rubric assessment about material of atoms, ions, and molecules for junior high school students. The results of the experts validation and trials at small and large groups indicate that the product is appropriate and effective to be tested in the field. Assessment instruments were developed to help teachers identify the creative thinking skills of junior high school students on atoms, ions, and molecules.